UNVEILING THE ANTIDIABETIC POTENTIAL OF KEMUNING LEAVES (Murraya paniculata L. Jack): AN IN-SILICO EXPLORATION OF DPP-4 INHIBITORY ACTIVITY - Ladika Wiratama, Arif; Aulia Nanda, Taurisma; Hidayah, Farsya; Weningtyas, Anditri (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Type 2 diabetes mellitus is a global health issue associated with insulin resistance and impaired glucose metabolism. Murraya paniculata L. Jack (kemuning) has shown antidiabetic potential, yet its role as a DPP-4 inhibitor remains underexplored. This study aimed to investigate the potential of kemuning leaf bioactive compounds as natural DPP-4 inhibitors through an in-silico approach. Compound structures were obtained from the PubChem database and analyzed using AutoDock Vina for molecular docking against the DPP-4 protein. Pharmacokinetic properties, toxicity, and drug-likeness were evaluated using pkCSM and SwissADME, while complex stability was assessed through molecular dynamics simulation (RMSF). The results showed that most compounds demonstrated favorable binding affinities (−6.8 to −7.9 kcal/mol), along with acceptable pharmacokinetic and toxicity profiles. Among the tested compounds, 1-aminoindan-1,5-dicarboxylic acid emerged as the most promising candidate for natural DPP-4 inhibition.